ANALISIS PERHITUNGAN, PENYETORAN, PELAPORAN, DAN PENCATATAN PAJAK PERTAMBAHAN NILAI PADA PT. XYZ - Andreas, Andreas; Kanti, Annisa (E-Jurnal Akuntansi TSM, 2024)
This research is conducted with the aim of analyzing the calculation, deposit, reporting, and recording of Value Added Tax (VAT) at PT. XYZ in the year 2023. This study compares whether the procedures for calculation, deposit, and reporting have complied with Law Number 7 of 2021 concerning Tax Regulation Harmonization. The research is also conducted to determine whether the procedures for recording Value Added Tax comply with the applicable general accounting standards for taxation. This research uses a qualitative descriptive analysis method. The research sources were obtained through direct work practices at PT. XYZ. The analyzed data includes VAT Periodic Tax Returns, Recapitulation of Value Added Tax Deliveries and Acquisitions, Value Added Tax Deposit Evidence, Value Added Tax Reporting Evidence, and Value Added Tax recording journals obtained directly from PT. XYZ. This study concludes that there is inconsistency in the calculation of Value Added Tax in the November Tax Period, caused by an error in the Sales Return rate. Deposits and reporting have complied with Law Number 7 of 2021. The recording is in accordance with the applicable general accounting standards for taxation.